Risks versus Costs: A New Approach for Assessment of Diffuse Water Pollution Abatement - Plunge, Svajunas (My University, 2009)
Complex problems require innovative methods to deal with them. Diffuse pollution, which is a primary reason for deterioration of many surface and groundwater bodies, has yet to obtain a reliable solution. This work is designated to be a part of such solution, which is to provide a valuable approach to manage inland surface water diffuse pollution problem. It is especially designed for decision makers responsible for implementation of Water Framework Directive. The key aspects of this approach are the integrating Environmental Risk Assessment and Cost- Effectiveness Assessment, which is a part of the framework used to evaluate diffuse pollution abatement measures. An extensive literature review has been made to examine integration possibilities in a wider perspective. Accomplishing this objective four separate topics were evaluated: review of watershed modeling approaches, Environmental Risk Assessment and Cost- Effectiveness Assessment in diffuse pollution problem solution, review of Lithuanian and European legislation on controlling the inland surface water diffuse pollution, inland water diffuse pollution abatement measures. Knowledge obtained from literature has been used to set a modeling part essential to demonstrate application of the integration method. SWAT model has been selected as the assessment tool to analyze diffuse pollution abatement measures for Graisupis river catchment, located in middle Lithuania. Two abatement measures (wetlands and winter crops) have been selected and evaluated. Finally, a risk reduction of not meeting environmental targets from the baseline scenario has been calculated and plotted against cost of each abatement measure. This is a simple way of providing valuable information needed for investments in abatement and uncertainties related to it, which are particularly important for decision makers working with diffuse pollution problems.
Keywords: Miljöteknik; Environmental engineering